Event-related theta synchronization over sensorimotor areas differs between younger and older adults and is related to bimanual motor control - Andreas Wulff-Abramsson; Ana Zvornik; Keenie Ayla Andersen; Yan Yang; Mikael Novén; Jesper Lundbye-Jensen; Leo Tomasevic; Anke Ninija Karabanov (NeuroImage)
When engaged in dynamic or continuous movements, action initiation involves modifying an ongoing motor program rather than initiating it from rest. Event-related theta synchronization over sensorimotor areas is a neurophysiological marker for modifying motor programs. We used electroencephalography (EEG) to examine how task complexity and age affect event-related synchronization (ERS) in the theta band during a dynamic bimanual, visuomotor pinch force task. Older (mean age = 68) and younger (mean age = 26) participants performed symmetric (SYM) and asymmetric (ASYM) bimanual pinch force adjustments. Trials began with a visually cued contraction from a baseline force to a novel target force (P1). Force had to be maintained at the target until a visually cued return to the familiar baseline (P2). Older adults reacted slower across task conditions, and their accuracy decreased more when shifting from the SYM to the ASYM condition. Older adults also displayed lower theta ERS across conditions. Additionally, older adults were not able to modulate theta expression based on whether a force change was initiated to a novel target or back to baseline. Younger adults showed significantly stronger theta ERS after P1-cues compared to P2-cues, while the theta response to P1 and P2 cues was not different in older adults. Older adults also showed stronger lateralization, displaying higher theta ERS over the dominant motor cortex. Finally, event-related theta synchronization appeared to be behaviorally relevant across groups and correlated with task performance. Together, the results show that theta ERS over sensorimotor areas is a strong, age-sensitive marker of dynamic pinch force adjustments showing an age-related reduction in specificity with reduced context-dependent modulations and more imbalanced bimanual activation.